Formulasi Transetosome Ekstrak Teh Hijau (Camellia sinensis L. Kuntze) Menggunakan Variasi Konsentrasi Soya Lesitin dan Etanol - Sofiani Lathifah; Kurniawan Kurniawan; Nadia Mira Kusumaningtyas (University Of Darussalam Gontor, 2022)
Green tea is a herbal plant that can be used to maintain health because of its high antioxidant compounds. Along with the development of pharmaceutical technology, drug delivery systems are also increasingly developing, one of which is transetosomes. The purposes of this study are to determine the effect of variations in the concentration of soy lecithin and ethanol on the characterization of transetosomes. Transetosomes are made using the heat method and formulated in 3 formulations with variations in the concentration of lecithin and ethanol, respectively (F1 0.5: 20, F2 0.6: 25, F3 0.7: 30). Based on the results of the study, obtained the best green tea extract transetosomes is in F3 where the resulting form is Unilamellar Vesicle with a size of 105.96 ± 18.94 nm and polydispersity index 0.36 ± 0.01.